Impact of a new case-based payment scheme on volume distribution across public hospitals in Zhejiang, China: does ‘Same disease, same price’ matter - Meiteng Yu; Jing Liu; Tao Zhang (International Journal for Equity in Health)
Abstract Background With the implementation of the hierarchical medical system (HMS) in China, Zhejiang Province introduced an innovative payment scheme called “payment method by disease types with point counting”. This scheme was initially adopted in Jinhua in July 2017, and was later integrated with the “same disease, same price” policy in Hangzhou in January 2020. This study aimed to investigate the impact of these reforms on the distribution of health service volume. Methods Data were obtained from 104 hospitals, including 12 tertiary and 14 secondary hospitals from each of four regions: Jinhua (intervention) vs. Taizhou (control), and Hangzhou (intervention) vs. Ningbo (control). A total of 3848 observation points were examined using two sets of controlled interrupted time series analyses to assess the effects of this new case-based payment, without and with “same disease, same price”, on the proportion of discharges, total medical revenue and hospitalization revenue. The Herfindahl–Hirschman Index (HHI) were analyzed to evaluate changes in market competition. Results Following the introduction of the new case-based payment without “same disease, same price”, secondary hospitals in Jinhua experienced a significant decline in the proportion of discharges (β6 = -0.1074, p = 0.047), total medical revenue (β6 = -0.0729, p = 0.026), and hospitalization revenue (β6 = -0.1062, p = 0.037) compared to those in Taizhou, while tertiary hospitals showed a non-significant increase. After incorporating “same disease, same price”, the proportion of discharges (β6 = 0.2015, p = 0.031), total medical revenue (β6 = 0.1101, p = 0.041) and hospitalization revenue (β6 = 0.1248, p = 0.032) in Hangzhou’s secondary hospitals increased compared with Ningbo’s, yet the differences in both the level and trend changes between tertiary hospitals in the two cities were not statistically significant. The HHI in Jinhua (β7 = 0.0011, p = 0.043) presented an upward trend during the pilot period of the case-based payment, while the HHI in Hangzhou (β6 = -0.0234, p = 0.021) decreased immediately after the introduction of “same disease, same price”. Conclusion This new case-based payment scheme may worsen the disproportionate distribution of service volume across hospitals of different levels. While “same disease, same price” shows potential benefits, further evidence is needed to assess its effectiveness in promoting HMS. Policymakers should consider hospital interests in payment design and address unintended strategic behaviors.